(untitled) (Journal of Ideas in Health, 2023)
Background: Globally, breast cancer is a widespread malignancy among women, ranking as the second leading cause of female mortality. This study investigates risk factors for breast cancer in AL-Anbar province, Iraq, emphasizing their significance in disease development. Methods: An investigation was carried out at Al-Anbar Cancer Center in Al-Anbar province, Iraq, employing a case-control design. The study comprised 60 confirmed breast cancer cases and 120 controls without breast issues. Data was collected through direct interviews using a semi-structured questionnaire, and subsequent analyses included descriptive, bivariate, and multivariate approaches. Results: About 48.0% aged 41-49, and 25% aged 50-59. Case and control groups were matched in age, but varied in marital, education, occupation, menopausal status. Women with benign breast diseases have a 1.7 times higher breast cancer risk (OR=1.7, CI=0.063-4.53). Positive family history triples the risk (OR=3, CI=1.21-7.80, P=0.002), and the sedentary lifestyle exhibits 5 times higher risk of breast cancer (OR=5.67, CI=2.89-4.13, P < 0.001). Menstrual age, parity, and reproductive factors influence breast cancer risk. Menarche at ≤12 years triples the risk (OR=3.05, CI=1.82-5.05, P<0.001), while menarche at ≥16 decreases it (OR=0.89, CI=0.06-5.12, P<0.001). Nulliparity increases risk 2.1 times (OR=2.1, CI=0.8-4.89, P=0.002), and more live births provide significant protection. Preterm delivery before the eighth month triples the risk (OR=2.9, CI=1.32-6.53, P=0.002). Multiple children prevent breast cancer, while mother’s age at first full birth ≥30 raises the risk 3.5 times (OR=3.4, CI=1.45-7.88, P=0.014). Women who never breastfed had a significant twofold higher risk of breast cancer (OR=2, CI=0.8-4.38, P=0.003). Postmenopausal women at ≥50 years faced a threefold higher risk than their counterparts (OR=3.25, CI=1-1.11, P=0.004). Hormonal use showed a marginal risk increase (OR=1.2, CI=0.5-1.8, P<0.001). Conclusion: Breast cancer susceptibility arises from diverse factors like genetics, nutrition, environment, and lifestyle. Effectively managing and preventing breast cancer involves implementing strategic control measures.